If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9w+42=3(w+8)
We move all terms to the left:
9w+42-(3(w+8))=0
We calculate terms in parentheses: -(3(w+8)), so:We get rid of parentheses
3(w+8)
We multiply parentheses
3w+24
Back to the equation:
-(3w+24)
9w-3w-24+42=0
We add all the numbers together, and all the variables
6w+18=0
We move all terms containing w to the left, all other terms to the right
6w=-18
w=-18/6
w=-3
| 7-14+3x=11 | | 3/3x=24 | | 130=4x-26+3x+4 | | 3/5x+8=29 | | -19x+5=8x+221 | | 19x-5(4x-6)=36 | | 10+5+6x=21 | | 180=11x+1 | | -37=3-5-5(5-3n) | | 8x3(7x6−3x5)=0 | | 3x^2+48x=180 | | -15x+6=21 | | 4x+30=5x10+3x-20 | | 0.3-0.5x+0.9=0.1x-0.4 | | -9x-7=-4x+3 | | 17.3x+11=2x+20 | | 3x-3+12=5x-2+9x | | 22x-14+6x+28=19 | | 250x-3=40x | | y+2y-4=5 | | 3(a+7)=-3(2a-1) | | 5v=–6+4v | | 11x-20=-19x-230 | | 0.6w-0.5=0.8w | | 3x=225/5x | | -x2-x-2=0 | | 4x+10=3x+56 | | 8x-32=-28 | | 12x-20=-19x-230 | | 4=3v+5 | | -10x+80=6x | | 4x+9=14x-91 |